AUTOMATED 3D CAMERA PLACEMENT - MOHAMMED YUSOFF, SITI KAMALIAH (2013)
This project aims to find the minimum number of cameras needed to observe given three-dimensional (3D) environment and the cameras placement. This report traces the structure of the algorithm used to find the optimal number and placement of the cameras, the deployment of the algorithm in camera placement system, and presents the results of testing done on the system. This study related to the well known Art Gallery Problem (AGP) that addressed the problem of finding minimum number of guards necessary to guard the art gallery. Since this problem was posed, much research has been done on solving the problem from two dimensional (2D) perspectives. Not much research is done from 3D perspective and only recently more researchers are interested to study this problem in 3D environment. F